An Analysis of the Earthenware Product's Formation Based on Jia Gu Wen's Calligraphy Identity - Luo, Bingsheng; Sankaburanurak, Atiyot (Journal of Posthumanism, 2025)
China has a long and illustrious history in producing earthenware that dates back thousands of years. The Neolithic Period is when the oldest pottery is known to have existed; it was hand-built and included elaborate decorations. The evaluation and publication of the formation of earthenware products are the research objectives. The study of the transition of Jia Gu Wen into ceramic pieces is a creative, multidisciplinary undertaking according to the research methodology. It integrates knowledge from several disciplines, such as ceramic design, Jia Gu wen calligraphy, philology, and sculpture. Examining the characteristics of Jia Gu Wen, incorporating those characteristics into ceramic works, promoting the findings, and investigating consumer satisfaction are the goals of this project. The results are that in the pottery, important elements including shape, spirit, glaze, and fire are taken into account. Jia Gu Wen is being transformed into ceramic works by a recent multidisciplinary invention. Research and experimentation are very beneficial. In conclusion, because of the continuous progress in archaeology and the continued abundance of cultural relics, research on the calligraphy of Jia Gu Wen and pottery has made considerable strides in the recent years. The increasing number of scholars are beginning to concentrate on this field and have in-depth discussions regarding Jia Gu Wen's calligraphy and ceramics from a variety of angles.